THE IMPACT OF JORDAN’S COUNTRY OF ORIGIN IMAGE ON THE MENTAL IMAGE CARRIED BY CLOTHING CUSTOMERS - Hashem, Tareq N.; Rislan Homsi, Diana; Qasheh, Renad Mohammad Abu; Al Sorike, Mohammad Hasan; Alasmar, Alaa Saleh (International Journal of Research -GRANTHAALAYAH, 2017)
The study aimed at examining the impact of Jordan’s country of origin image on the mental image carried by clothing customers. The used descriptive and analytical approach in which a questionnaire was used to collect the needed data from the sample of the study. A convenience sample consisted of 400 employees. The data were analyzed through using SPSS. The study found that Jordanian consumers had positive attitudes towards it as a country of origin. Country of origin image has an impact on the mental image carried by clothing customers. The study also found that there is a statistical difference in impact of Jordan’s country of origin image on the mental image carried by clothing customers due to Educational level only. Moreover the study found that there are no statistical differences in impact of Jordan’s country of origin image on the mental image carried by clothing customers due to (Gender and age). The study recommended that Jordanian institutions must set a comprehensive strategy for raising the quality of their products. That is because quality has a major impact upon enhancing the image of the country of origin and upon the way its products are evaluated. In addition national institutions must be more concerned with conducting more research and improvements in order to raise their levels of innovation and technological developments in clothing sector.